2002
DOI: 10.1046/j.1365-2958.2002.02960.x
|View full text |Cite
|
Sign up to set email alerts
|

A signal transduction system in Streptomyces coelicolor that activates the expression of a putative cell wall glycan operon in response to vancomycin and other cell wall‐specific antibiotics

Abstract: SummaryWe have investigated a signal transduction system proposed to allow Streptomyces coelicolor to sense and respond to changes in the integrity of its cell envelope. The system consists of four proteins, encoded in an operon: s E , an RNA polymerase s factor; CseA (formerly ORF202), a protein of unknown function; CseB, a response regulator; and CseC, a sensor histidine protein kinase with two predicted transmembrane helices (Cse stands for control of sigma E). To develop a sensitive bioassay for inducers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
113
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 101 publications
(123 citation statements)
references
References 34 publications
4
113
0
1
Order By: Relevance
“…These results demonstrate that DivIVA is indeed subject to phosphorylation, that there is a low but significant basal level of DivIVA phosphorylation (as detailed later) during undisturbed vegetative growth in liquid medium, and that DivIVA phosphorylation increases dramatically when cell wall synthesis is blocked. Previous studies have shown that Streptomyces has a signal transduction system, the CseB/CseC-σ E system, which is involved in sensing and responding to changes in the integrity of the cell envelope, and that inducers of this system include antibiotics that inhibit cell wall synthesis such as bacitracin and vancomycin (31). To test whether the CseB/CseC-σ E system might be involved in mediating the increase in DivIVA phosphorylation observed when cell wall synthesis is blocked as part of this general cell envelope stress response, we analyzed immunoprecipitated DivIVA material from a sigE-null mutant.…”
Section: Diviva Phosphorylation Increases Dramatically When Cell Wallmentioning
confidence: 99%
“…These results demonstrate that DivIVA is indeed subject to phosphorylation, that there is a low but significant basal level of DivIVA phosphorylation (as detailed later) during undisturbed vegetative growth in liquid medium, and that DivIVA phosphorylation increases dramatically when cell wall synthesis is blocked. Previous studies have shown that Streptomyces has a signal transduction system, the CseB/CseC-σ E system, which is involved in sensing and responding to changes in the integrity of the cell envelope, and that inducers of this system include antibiotics that inhibit cell wall synthesis such as bacitracin and vancomycin (31). To test whether the CseB/CseC-σ E system might be involved in mediating the increase in DivIVA phosphorylation observed when cell wall synthesis is blocked as part of this general cell envelope stress response, we analyzed immunoprecipitated DivIVA material from a sigE-null mutant.…”
Section: Diviva Phosphorylation Increases Dramatically When Cell Wallmentioning
confidence: 99%
“…The predicted functions of the enzymes encoded by this operon strongly suggest that the operon specifies the synthesis of a species of cell wall glycan (hence the operon has been named cwg). High resolution S1 nuclease mapping showed that the putative -10 and -35 sequences identified by computer searching do indeed correspond to a bona fide promoter, and that the cwg promoter is induced by vancomycin in a sigE-dependent manner 12) . Thus a set of genes under σ E control has been identified that has a clear cell envelope-related function, and transcription of these genes has been shown to be induced by vancomycin and, presumably therefore, other cell wall-targeted antibiotics and enzymes.…”
Section: Csea Has a Negative Role In The Sige Signal Transduction Systemmentioning
confidence: 98%
“…In an attempt to better understand the nature of the signal sensed by CseC, we developed a bioassay to test for compounds that induced the sigE promoter 12) The sigE promoter was placed upstream from a plasmid-borne In response to signals that originate in the cell envelope when it is under stress, the sensor kinase, CseC, becomes autophosphorylated at His-271, and, in accordance with the known mechanism for other two-component regulatory systems, this phosphate is then transferred to Asp-55 in the response regulator, CseB. Phospho-CseB activates the promoter of the sigE operon, and σ E is recruited by core RNA polymerase to transcribe genes with cell envelope-related functions.…”
Section: Evidence For the Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, an understanding of resistance determinants present in the soil-the soil 'resistome'-will provide information not only about frequencies of antibiotic resistance emergence but also about new mechanisms that may emerge as clinical problems." Examples of the evolution of highly specific resistance elements include vancomycin resistance in Streptomyces coelicolor, Paenibacillus (which can cause meningitis, pneumonia, and septicemia in humans), and Rhodococcus, a cause of infection in grazing animals (3,5,6).…”
Section: Resistance: Natural Origins Plus Human "Help"mentioning
confidence: 99%